Synchronous population fluctuations of forest and field voles: implications for population management - Tkadlec, E.; Suchomel, J.; Purchart, L.; Heroldová, M.; Čepelka, L.; Homolka, M. (Julius Kühn-Institut, 2011)
High population densities of field and forest voles cause economic losses by consuming crop or slowing down forest regeneration by damaging the bark of young trees. Consequently, programs to monitor abundances are often implemented as part of population management. Whereas abundances of the common vole (Microtus arvalis) in the Czech Republic has regularly been checked by the State Phytosanitary Administration for decades, no monitoring program has so far been invented to monitor forest voles. Because population numbers of different vole taxa are often observed to fluctuate in phase, we explored the possibility whether the monitoring data for the common vole can be used to forecast numbers of forest voles. Since 2002, we have monitored by snap-trapping bank vole (Myodes glareolus) populations in three forests situated in southern Moravia, Czech Republic. Correlation analysis of time series of yearly population changes for the common and bank vole revealed that populations of field and forest voles in southern Moravia fluctuate in a close synchrony, the correlations being consistently higher than 0.8. This result provides the reasonable possibility of exploiting the data from the extensive